Zivotní príbeh profesora Josefa Hohlbauma - Stingl, J; Kästner, I; Mísková, A; Musil, V (Rozhledy v chirurgii, 2009)
Professor Josef Hohlbaum (*Sept. 6, 1884 in Oberlindewiese, Northern Moravia) studied medicine in Graz, Austria. His main place of work was Leipzig, Germany, where he became an outstanding surgeon and a very good university teacher. Between 1941 and 1945, he was the last chairman of Surgery of the German University in Prague. On May 9, 1945, he was arrested by the Czech police and imprisoned in the internment camp in Klecany. At the end of June 1945, during farming work, his left leg was seriously injuried by an explosive, found by a Czech guard and thrown under Hohlbaums' foot. J. Hohlbaum received first wound treatment and was admitted to the Surgical Department of the Královské Vinohrady Hospital in Prague 10, where he spent 6 weeks. Thereafter, at his request, he was transferred to the German Military Hospital in Prague 5. During the autumn of 1945, he was transferred to Germany, his condition grew more and more worse, and, consequently, his left lower extremity had to be amputated in femore. On December 30, 1945, he died of sepsis in the Surgical department of the Hospital in Markkleeberg, near Leipzig. The authors could not find any evidence that Hohlbaums' professional contemporary, the Czech surgeon professor A. Jirásek, presented a non-ethical attitude to the injured J. Hohlbaum, and that Jirásek refused to treat him, as it has been repeatedly presented in German publications. On the contrary, it is evident from the documents found, that the care he got in Prague--with respect to the difficult circumstances--was lege artis. Hohlbaunt's life thus ended as a consequence of the situation at the end of WWII.
Keywords: Czechoslovakia; Germany; World War II; dějiny 20. století; lidé; History, 20th Century; Humans; chirurgie; 2. světová válka; Československo; Německo; General Surgery